Psychrothrophic bacteria and thermosist resistant enzymes in raw milk - Nunes, Kleber Barros; Silva, Livia Ribeiro da; Silva, Sybelle Georgia Mesquita da; Cavalcanti Neto, Cícero; Santos, Tania Marta Carvalho dos; Montaldo, Yamina Coentro (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The goal of this study was the isolation and biochemical characterization of psychotrophic microbiota, evaluating its deteriorating potential on refrigerated raw milk stored in both individual and collective expansion tanks located in farms from Agreste and Sertão regions of Alagoas State. Milk samples from 23 (individual) and 13 (collective) tanks were analyzed, and the presence of psychotropic bacteria was diagnosed in both types of refrigeration tanks, totalizing 105 bacterial isolates. There was a predominance of gram-negative psychotropic bacteria 78,09% (82/105) from genus Pseudomonas, Enterobacter, Aeromonas, Burkholderia, Acinetobacter e Shigella, whereas gram-positive bacteria represented 21,90% (23/105) of total isolates, from genus Streptococcus, Corynebacterium, Enterococcus, Micrococcus and Bacillus. In general, Pseudomonas was the most prevalent genus isolated 43,81% (46/82). The majority of bacterial isolates had high extracellular enzymes production – protease, lipase and/or lecithinase, which evidenced elevate deteriorating potential for milk and its derivatives. There was no significant difference on enzymatic production among isolates or between individual and collective tanks, as well as no dependency between total number of enzymatic producer bacterial isolates and tank type.